Looks like no one added any tags here yet for you.
lnx
∫x1 (1/t) x>0
ln(ab)
ln(a) + ln(b)
ln(a/b)
ln(a)-ln(b)
ln(an)
nln(a)
ln(1)
0
ln(e)
1
b=ea
lnb=a
c=ab
logac=b
logax
(lnx)/(lna)
lnex
x
elnx
x
logaax
x
alogax
x
exlna
ax
d/dx(lnx)
1/x
d/dx(lnu)
u’/u
∫1/x dx
ln|x| + C
∫sinxdx
-cos(x) + C
∫cosxdx
sin(x) + C
∫tanxdx
-ln|cos(x)| + C
∫cotxdx
ln|sin(x)| + C
∫secxdx
ln|secx+tanx| + C
∫cscxdx
-ln|cscx+cotx| + C
d/dx(ex)
ex
d/dx(eu)
eu * u’
∫exdx
ex + C
∫eudu
eu + C
d/dx(ax)
axlna
d/dx(au)
au*lna*u’
∫axdx
ax/lna + C
d/dx(logax)
1/xlna
d/dx(logau)
u’/ulna
if g(x)=f-1(x), g’(x)=
1/f’(g(x))
d/dx(sinx)
cosx
d/dx(cosx)
-sinx
d/dx(tanx)
sec2x
d/dx(secx)
secxtanx
d/dx(cscx)
-cscxcotx
d/dx(cotx)
-csc2x